De Novo Sequencing and High-Contiguity Genome Assembly of Moniezia expansa Reveals Its Specific Fatty Acid Metabolism and Reproductive Stem Cell Regulatory Network - Liu, Yi; Wang, Zhengrong; Huang, Wanlong; Pang, Shuai; Qian, Lingxiao; Zhang, Yanyan; Meng, Jimeng; Xu, Mengfei; Wang, Weiyi; Wang, Yunfei; Lu, Baoyan; Zhao, Yiyue; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Moniezia expansa (M. expansa) parasitizes the small intestine of sheep and causes inhibited growth and development or even death. Being globally distributed, it causes considerable economic losses to the animal husbandry industry. Here, using Illumina, PacBio and BioNano techniques, we obtain a high-quality genome assembly of M. expansa, which has a total length of 142 Mb, a scaffold N50 length of 7.27 Mb and 8,104 coding genes. M. expansa has a very high body fat content and a specific type of fatty acid metabolism. It cannot synthesize any lipids due to the loss of some key genes involved in fatty acid synthesis, and it may can metabolize most lipids via the relatively complete fatty acid β-oxidation pathway. The M. expansa genome encodes multiple lipid transporters and lipid binding proteins that enable the utilization of lipids in the host intestinal fluid. Although many of its systems are degraded (with the loss of homeobox genes), its reproductive system is well developed. PL10, AGO, Nanos and Pumilio compose a reproductive stem cell regulatory network. The results suggest that the high body lipid content of M. expansa provides an energy source supporting the high fecundity of this parasite. Our study provides insight into host interaction, adaptation, nutrient acquisition, strobilization, and reproduction in this parasite and this is also the first genome published in Anoplocephalidae.